The implementation of peer tutoring through lesson study to develop learners` collaborative and communicative skills - Yentri Anggeraini (English Language Education Study Program, Teacher Traning and Education Faculty, Universitas Muhammadiyah Cirebon, 2023)
The purpose of this study is to investigate the implementation of peer tutoring through lesson study in developing candidate English teachers` collaborative and communicative skills. The sample of this study was 22 third-semester students who joined the speaking for professional contexts course. In order to gather the data, three steps (plan, see, and do) were applied. The first is having a discussion with the teacher and the headmaster to analyse the students` needs, the current situation of the teaching strategies, and problems or challenges in the classroom. Second, observation of three learning sessions with the implementation of peer tutoring through lesson study. It covers observation notes, reflections, and video recordings. Then, the data were analysed descriptively. The result showed that the students had made progress in developing collaborative and communicative skills, improved trusting relationships and supportive behaviours among classmates, and developed confidence in expressing themselves, representing themselves, and accepting other opinions while speaking. Keywords: peer tutoring; speaking; collaboration; communicative; lesson study